To Provide or Protect? Masculinity, Economic Precarity, and Protective Gun Ownership in the United States. (February 2022) - Warner, Tara D.; Tober, Tara Leigh; Bridges, Tristan; Warner, David F.
Protection is now the modal motivation for gun ownership, and men continue to outnumber women among gun owners. While research has linked economic precarity (e.g., insecurity and anxiety) to gun ownership and attitudes, separating economic well-being from constructions of masculinity is challenging. In response to blocked economic opportunities, some gun owners prioritize armed protection, symbolically replacing the masculine role of "provider" with one associated with "protection." Thus, understanding both persistently high rates of gun ownership in the United States (in spite of generally declining crime) alongside the gender gap in gun ownership requires deeper investigations into the meaning of guns in the United States and the role of guns in conceptualizations of American masculinity. We use recently collected crowdsourced survey data to test this provider-to-protector shift, exploring how economic precarity may operate as a cultural-level masculinity threat for some, and may intersect with marital/family status to shape gun attitudes and behaviors for both gun owners and nonowners. Results show that investments in stereotypical masculine ideals, rather than economic precarity, are linked to support for discourses associated with protective gun ownership and empowerment.